Neuroscience: Domestication shaped dogs’ brains and behaviour - Marike Schiffer (Communications Psychology)
Dogs have worked and lived with humans for thousands of generations. Modern dogs’ looks and behaviour differ substantially from wolves’. A study in Journal of Neuroscience compares the behaviour and brains of modern and pre-modern dogs to understand the course of wolf-to-dog domestication.